Un texto olvidado de Juan Pablo Forner: la comedia, para funciones múltiples, de Los aduladores - Piedad Bolaños Donoso; Jesús Cañas Murillo (Cuadernos de Ilustración y Romanticismo, 2021)
This article rescues from oblivion one of the few plays composed by Juan Pablo Forner in the Spanish Eighteenth Century that we have preserved, but of which there was no news at the present time. It is a comedy, Los aduladores, which was premiered posthumously in Madrid, at the Teatro de la Cruz, in 1797. In this paper, the first printed version of Los aduladores since the time it was written is included. The edition is based on the three manuscripts of the text preserved in the Municipal Historical Library of Madrid, the only sources until now known that transmit it. In the introductory study, comedy is also framed in the group of eighteenth-century theatrical creations, to which, by its compositional characteristics, it belongs.